Transparansi dan Akuntabilitas Pengelolaan Infaq Ramadhan Dalam Meningkatkan Kepercayaan Jamaah: Studi Kasus di Masjid Imanuddin (Desa Carebbu Kabupaten Bone Sulawesi Selatan) - Eliana Eliana; Yusuf, Muhammad; Hasbi, Hartas (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study examines the forms of transparency and accountability in managing Ramadan infaq to enhance congregational trust: A Case Study at Imanuddin Mosque (Carebbu Village, Bone Regency, South Sulawesi). The research aims to analyze the transparency and accountability of Ramadan infaq management at Imanuddin Mosque. Transparency and accountability are critical elements in managing religious funds to ensure public trust in mosque administrators. The study employs a descriptive qualitative approach with data collection techniques through interviews. The findings reveal that Imanuddin Mosque has implemented several principles of transparency by periodically reporting infaq funds to the congregation. However, challenges remain in terms of accountability; while the mosque administrators attempt to account for the funds to the congregation through regular reporting, they have yet to involve independent audits. The study recommends strengthening reporting systems and involving external parties to enhance public trust in the management of Ramadan infaq.